Synthesis Of Silicon Nanowires By Carbothermal Evaporation Method Using Metal Catalyst - Bahrin, Muhamad Dzulnawarin Kamal (Universiti Sains Malaysia, 2017)
Silicon nanowires (SiNWs) have successfully been synthesised by carbothermal evaporation method with the use of catalyst. SiNWs with the diameter range of with 45 nm to 65 nm and from 35 nm to 65 nm were grown by using gold nanoparticles (AuNPs) and nickel (Ni) catalyst respectively. Carbothermal evaporation method was utilised since the procedure is simple and inexpensive. The precursor used was the 1:1 mixture of silicon powder with activated carbon powder. The precursor was heated in an inert furnace atmosphere. The furnace was ramped up at 20 oC/min to reach the temperature of 1100 oC. The evaporated silicon powder was carried by flowing nitrogen gas and was deposited on the surface of (111) silicon substrate. By controlling the physical parameters such as heating rate, growth temperature and time, substrate position and location the morphology and chemical composition of deposited products were evaluated by various characterization techniques. SiNWs were grown at 1100 oC after 1 hour and 5 hours with the use of Ni and AuNPs catalyst respectively. The silicon substrate was placed 12 cm away from the precursor vertically. Based on the experimental results, it can be said the SiNWs were synthesised using the vapour-liquid-solid (VLS) growth mechanism.